Influence of lactulose as a composition of organic-mineral feed additive on broiler chicken productivity, feed digestibility, and microbiome - Еlena A. Sizova; Daniil E. Shoshin; Еlena V. Yausheva; Anastasia P. Ivanishcheva; Ksenia S. Nechitailo; Kristina V. Ryazantseva (Veterinary World)
Background and Aim: The global demand for efficient poultry production necessitates alternatives to antibiotic growth promoters. This study aimed to evaluate the effects of a novel four-component organic-mineral feed additive (OMFA), comprising lactulose, arginine, ultrafine silicon dioxide particles, and succinic acid, and a three-component variant (without lactulose) on growth performance, nutrient digestibility, elemental tissue composition, and the cecal microbiota of Arbor Acres broiler chickens.